2012
DOI: 10.1590/s0074-02762012000900028
|View full text |Cite
|
Sign up to set email alerts
|

Insights from animal models on the immunogenetics of leprosy: a review

Abstract: A variety of host immunogenetic factors appear to influence both an individual's susceptibility to infection with Mycobacterium leprae and the pathologic course of the disease. Animal models can contribute to a better understanding of the role of immunogenetics in leprosy through comparative studies helping to confirm the significance of various identified traits and in deciphering the underlying mechanisms that may be involved in expression of different disease related phenotypes. Genetically engineered mice,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 67 publications
0
32
0
7
Order By: Relevance
“…A total of 6% of animals screened (all resistant to the disease) showed that homozygous G/G allele is associated with resistance to the disease (28).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 6% of animals screened (all resistant to the disease) showed that homozygous G/G allele is associated with resistance to the disease (28).…”
Section: Resultsmentioning
confidence: 99%
“…Freshly harvested bacilli are stored at 4°C and used within 24 hours of harvest [9]. In this study, BALB/c and athymic nu/nu mice (Harlin Sprague-Dawley, Inc., Indianapolis, IN) were infected by inoculating each hind FP with 3×10 7 M. leprae in 0.03 ml PBS (Irvine Scientific, Santa Ana, CA) [33], [34]. FPs were harvested on Day 1 post infection and at 4, 8, 12 and 17 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…This technique has been applied not only to skin biopsy samples, but also to several different types of specimens such as skin smears, nerves, urine, oral or nasal swabs, blood, and ocular lesions [11], [35][41]. Different sequences were used as targets for PCR, such as genes encoding the 36-kDa antigen [42], 18-kDa antigen [43], 65-kDa antigen [44], complex 85 [37], 16S rDNA [45], and the repetitive sequences [46] among other M. leprae genes. More recently, real-time PCR technology has improved detection, increasing sensitivity and specificity as it appears to be a robust tool for mycobacteria recognition in selected clinical situations, as well as for quantitation in experimental settings [37], [45], [47][50].…”
Section: Pcr As a Detection Toolmentioning
confidence: 99%